2021
DOI: 10.1525/elementa.2020.00157
|View full text |Cite
|
Sign up to set email alerts
|

Satellite detection of dinoflagellate blooms off California by UV reflectance ratios

Abstract: As harmful algae blooms are increasing in frequency and magnitude, one goal of a new generation of higher spectral resolution satellite missions is to improve the potential of satellite optical data to monitor these events. A satellite-based algorithm proposed over two decades ago was used for the first time to monitor the extent and temporal evolution of a massive bloom of the dinoflagellate Lingulodinium polyedra off Southern California during April and May 2020. The algorithm uses ultraviolet (UV) data that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Given the relationship between diatoms, porphyra-334, and silica present at the polar front, porphyra-334 may serve as an alternate proxy for the location of the PF zone. Kahru et al (2021) demonstrated the ability to differentiate neighboring algal blooms of differing taxonomic composition via the remote detection of UVR spectral bands, likely due to the presence of MAAs. However, this differentiation was hypothesized to be based on the presence of the MAA palythene, which has a peak absorption at 360 nm in the long-wavelength UVA region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the relationship between diatoms, porphyra-334, and silica present at the polar front, porphyra-334 may serve as an alternate proxy for the location of the PF zone. Kahru et al (2021) demonstrated the ability to differentiate neighboring algal blooms of differing taxonomic composition via the remote detection of UVR spectral bands, likely due to the presence of MAAs. However, this differentiation was hypothesized to be based on the presence of the MAA palythene, which has a peak absorption at 360 nm in the long-wavelength UVA region.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, observed variability in MAA production as a function of season (i.e., summer peak) and depth (surface maximum) suggest a tight coupling between the magnitude of UVR forcing and physiological response in phytoplankton and other marine organisms (Morrison and Nelson, 2004;Nuñez-Pons et al, 2018 and references therein), while the inability of certain species to produce MAAs imply that UVR may act as a forcing on phytoplankton community composition (Ha et al, 2018;Nuñez-Pons et al, 2018). In the future, absorption of UVR by MAAs may enhance satellite taxonomic characterization via remote sensing of UVR spectral bands (Kahru and Mitchell, 1998;Kahru et al, 2021). Recently, Kahru et al (2021) demonstrated that remote detection using UVR spectral bands was able to differentiate neighboring algal blooms of differing taxonomic composition, likely due to the presence of MAAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Plankton, Aerosol, Cloud, ocean Ecosystem (PACE) project will help with large-scale detection, collecting high-resolution data in the ultraviolet spectral band, recently shown to distinguish blooms of the dinoflagellate Lingulodinium polyedra. Other products including chl-a, net primary production, phytoplankton pigment concentrations, and spectral phytoplankton absorption coefficients will help measure biomass and decipher phytoplankton groups and species from one another [32,33]. The PACE satellite may be able to distinguish the spectral signature of Alexandrium around Tasmania, helping to detect and monitor the spatial extent [32].…”
Section: Discussionmentioning
confidence: 99%
“…Contamination by reflected light off ship structures or possibly associated with foam or wave facets may have also been a factor. While our application of the phytoplankton size class algorithm would be expected to be relatively insensitive to uncertainties in wavelengths at 412 nm or less, accurate estimates of Rrs in this wavelength range could nonetheless be very useful for certain applications such as characterizing properties of organic matter [41] and possibly certain phytoplankton classes [42]. Further investigation of the sources of variability in UV Rrs is warranted.…”
Section: Utility Of Hyperspectral Underway Reflectancementioning
confidence: 99%